Implementation of unit selection by using euclidean distance in malay text to speech [electronic resource] - 237893 Khor, Ai Ping; Fakulti Kejuruteraan Elektrik (2007)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Komputer)) - Universiti Teknologi Malaysia, 2007